Evaluating the effectiveness of outdoor evaporative cooling in a hot, arid climate. (March 2019) - Dhariwal, Jay; Manandhar, Prajowal; Bande, Lindita; Marpu, Prashanth; Armstrong, Peter; Reinhart, Christoph F.
Abstract: In a previous paper, we presented a novel approach to validate the capability of the biometeorological index, Universal Thermal Climate Index (UTCI), to predict the likelihood of urban dwellers to be outside in a public space for the heating dominated climate of Cambridge, MA. Occupancy patterns were recorded based on Wi-Fi data. The present study extends this approach to the hot and arid climate of United Arab Emirates (UAE) to evaluate the effect of outdoor evaporative coolers on resident presence in a public courtyard. Over a period of ten months, outdoor Wi-Fi access point data was collected in the public courtyard located on a university campus in Abu Dhabi. An analysis of the resulting MacID probes yields a population of 1200 regulars and 3800 visitors present in the courtyard at some point during the study period. Coincident UTCI simulations using ENVI-met strongly correlated with the number of regulars present during lunchtime both during times when the evaporative coolers were on (R 2  = 75%) and off (R 2  = 61%). Lunchtime attendance peaked for UTCI values in the thermal comfort range of around 24 °C during all seasons. The outdoor evaporative coolers were able to bring the UTCI down from very strong heat stress to between thermal comfort and moderate heat stress range. These findings confirm that UTCI can be used as a reliable environmental performance metric to support the design and preservation of comfortable outdoor spaces both in a hot and a cold climate, across a variety of cultural settings. Highlights: Wi-Fi data used to study the dwelling patterns of 5, 000 individuals in outdoor public spaces in Masdar Institute, Abu Dhabi. Lunchbreak patterns of 1, 200 regulars correlated with Universal Thermal Climate Index (UTCI) simulations. The outdoor evaporative coolers are effective for thermal comfort in the hot and arid climate of Abu Dhabi. UTCI is a reliable performance metric for the design of outdoor spaces in both a hot and a cold climate.